Potential of experimental activities in Chemistry Education - Santos, Diego Marlon (2017)
Pedagogical practices such as experimental activities are fundamental in the teaching of chemistry, since they are an efficient way in disseminating the contents, and support in the construction of knowledge, motivating the student to desire for knowledge, avoiding the routine of a technicalist teaching. This work was carried out according to the assumptions of the qualitative research with 3rd and 5th grade students, with the objective of investigating the students' opinion about the experimental activity on the extraction of essential oil of clove, was performed by means of a questionnaire. Regarding the methodology, in order to increase the efficiency of the learning process, the activities were conducted with ample questioning by the students, encouraging them to seek explanations for the studied phenomena. It was observed that most of the students showed an interest leaving them motivated in the process of teaching and learning, because it is a methodology that offers the student more chances to observe, analyze and discuss in groups the results achieved. However, we must consider that the important thing is the cognitive challenge that the experiment offers and not the simple handling of equipment and glassware.